PB

Cho hệ phương trình 2 3 x − 9 y + 6 x + y = 3 4 x − 3 y − 9 x + y = 1 y ≥ 0 ; x ≠ 3 y .

Nếu đặt 1 x − 3 y = a ; 1 x + y = b  ta được hệ phương trình mới là:

A.  1 2 a + 1 6 b = 3 1 4 a − 1 9 b = 1

B.  2 a + 6 b = 3 4 a − 9 b = 1

C.  2 b + 6 a = 3 4 b − 9 a = 1

D.  2 3 a + 6 b = 3 4 a − 9 b = 1

CT
16 tháng 3 2018 lúc 3:33

Ta có  2 3 x − 9 y + 6 x + y = 3 4 x − 3 y − 9 x + y = 1 ⇔ 2 3 . 1 x − 3 y + 6. 1 x + y = 3 4. 1 x − 3 y − 9. 1 x + y = 1

Đặt 1 x − 3 y = a ; 1 x + y = b  ta được hệ phương trình  2 3 a + 6 b = 3 4 a − 9 b = 1

Đáp án: D

Bình luận (0)